The purpose of this research is to study the effect of pyrolysis temperature to the wood vinegar chemical composition by be produced wood vinegar, charcoal, biofuel etc. The variation of pyrolysis temperatures were 110, 200, 300, 400 and 500 °C at 5 hours. That pine wood vinegar yield obtained were 13.80%, 16.12%, 11.99%, 15.51% and 0.90 %. Analysis DTA (Diferential Thermal Analysis) showed thermal decompotition occurs at 227, 320.2 and 349.7 °C. Identification of GC-MS of pine sawdust c - Mohammad WIJAYA; Erliza NOOR; Tun Tedja IRAWADI; Gustan PARI (Jurnal Ilmu dan Teknologi Hasil Hutan, 2008)
The purpose of this research is to study the effect of  pyrolysis temperature to the wood vinegar chemical composition by be produced wood vinegar, charcoal, biofuel  etc. The variation of pyrolysis  temperatures were 110, 200, 300, 400 and 500 °C at 5 hours. That pine wood vinegar yield obtained were 13.80%, 16.12%, 11.99%, 15.51% and 0.90 %.  Analysis  DTA (Diferential Thermal Analysis)  showed thermal decompotition occurs at  227, 320.2 and 349.7 °C.  Identification of GC-MS of pine sawdust could provide compounds that mostly derived from acid group and was dominated by acetic acid produced was 31.65%. At distillate of teak smokes was obtained three yield of liquid smokes resulted from conversion of pine wood  wastes can be utilized to preserve fishes.   Keywords :  Pine sawdust,  pyrolysis, wood vinegar, and preserve  fishes